Enhancing Disaster Awareness - SDG 13th Goals Mid-term Review of Disaster Impact Global Natural Disaster Reduction Effectiveness Before and After the 2015 Sendai and Paris Agreement Conferences - Liu , Ying-Yun; Lin , Tsan-hwan Percy (Journal of Ecohumanism, 2024)
The IPCC AR5 WGⅠhighlighted four priority areas for disaster risk reduction, with the first being the understanding of disaster risk. Meanwhile, the Earth is increasingly responding to climate change through natural disasters. This study proposes a Natural Disaster Impact Evaluate Formula （NDIEF）, focusing on six continents and utilizing data from 12 types of natural disasters recorded in the CRED EM-DAT database. The analysis is divided into two periods, before and after 2015, to evaluate changes over time. The findings reveal three key trends: First, the frequency of natural disasters continues to rise. Second, although the number of fatalities has significantly decreased, both exposure levels and economic losses have surged. Lastly, unlike the 2011 Global Assessment Report （GAR）, this study finds that the impact of natural disasters is not only severe in Oceania and island nations but is also increasingly affecting North America, particularly in terms of economic damage. In conclusion, enhancing our understanding of the social and economic impacts of natural disasters and raising awareness of disaster prevention can play a crucial role in effectively mitigating disaster risks.